Fostering Internal Pay Equity Through Gender Neutral Job Evaluations: A Case Study of the Federal Job Evaluation System. - Chordiya, Rashmi; Hubbell, Larry (Public Personnel Management, 2023)
The principle of pay equity implies that work determined to be equally demanding in terms of skills or qualifications, responsibilities, efforts, and working conditions should be valued and paid equally. However, prevailing gender-based stereotypes and prejudices about female-dominated jobs get in the way of achieving pay equity. Gender biases in compensable job (sub) factors could result in undervaluation and/or omission of relevant job (sub) factors associated with female-dominated jobs, and/or unbalanced/biased interpretation of job (sub) factors by associating them mostly with male-dominated jobs. Using a case study of the Federal job evaluation system for white-collar, non-supervisory Federal jobs the present article argues for a proactive and an intentional inclusion of gender-neutral (sub) factors in job evaluation systems in service of fostering internal pay equity within organizations.